Virtual Patient Case #4: Mrs. Violetta Mitsuko Tang - Chief Diagnosis: Osteoporosis/Incontinence - Kathryn Denson (Association of American Medical Colleges, 2007)
Abstract This resource contains the virtual patient case of Mrs. Violetta Mitsuko Tang, a geriatric patient diagnosed with osteoporosis and incontinence. This case is part of a series of virtual patient cases designed to allow facilitators to demonstrate how to care for an aging population. This case contains screening/diagnostic test results, radiographic images, still pictures, genograms, and narrative case presentations. One- to three-minute long video clips depicting the patients as she ages over a 15-25 year span are also included, and these clips have been explicitly designed to limit references to specific treatments (e.g., medications) or other aspects of care that may be time-limited. A technical manual with instructions on how to administer the module is also provided. In this particular case, Mrs. Tang initially presents as a 65-year-old Japanese-American, with a history of hypertension, mild hyperthyroidism, and hip pain. Over time she develops chest pain, atrial fibrillation, degenerative joint disease, osteoporosis, and incontinence through age 80. Unique digital resources available on this resource include bone density studies, biofeedback for incontinence with computer display, interactions with array of health care professionals (e.g., physical therapist, social worker), audiogram, thyroid histology, compression fracture, and EKG. TThe flexibility and quality of virtual patient resources such as these has been attested to by both basic science and clinical faculty to enhance core curriculum lectures. This resource may also serve as problem-based core case (since facilitators access resources in response to learner questions/issues during the tutorial), an e-learning application, and, in aggregated form, a longitudinal presentation of a geriatric patient. Ultimately, the effectiveness of these resources is dependent on the creativity of faculty who determine what, how, and when the resources are incorporated into new and/or established curriculum.